2020
DOI: 10.1002/oby.22756
|View full text |Cite
|
Sign up to set email alerts
|

Time‐Restricted Eating Effects on Body Composition and Metabolic Measures in Humans who are Overweight: A Feasibility Study

Abstract: Objective: In contrast to intentionally restricting energy intake, restricting the eating window may be an option for treating obesity. By comparing time-restricted eating (TRE) with an unrestricted (non-TRE) control, it was hypothesized that TRE facilitates weight loss, alters body composition, and improves metabolic measures. Methods: Participants (17 women and 3 men; mean [SD]: 45.5 [12.1] years; BMI 34.1 [7.5] kg/m 2 ) with a prolonged eating window (15.4 [0.9] hours) were randomized to TRE (n = 11: 8-hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
462
3
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(504 citation statements)
references
References 39 publications
23
462
3
16
Order By: Relevance
“…Fat mass, blood pressure, and lipids were not measured in this study because they posed additional logistical hurdles for a virtual study. However, weight loss of at least 5% is associated with clinically meaningful improvements in cardiovascular risk factors such as fat mass, visceral adipose mass, systolic and diastolic blood pressure, LDL-cholesterol, HDL-cholesterol, and triglycerides 1 , 2 , and have been documented in some studies of TRE 1 5 , 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fat mass, blood pressure, and lipids were not measured in this study because they posed additional logistical hurdles for a virtual study. However, weight loss of at least 5% is associated with clinically meaningful improvements in cardiovascular risk factors such as fat mass, visceral adipose mass, systolic and diastolic blood pressure, LDL-cholesterol, HDL-cholesterol, and triglycerides 1 , 2 , and have been documented in some studies of TRE 1 5 , 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The cardiometabolic effects of TRE in humans has only recently begun to be explored, and the majority of clinical trials investigating the effects of TRE on body weight are small pilot studies 3 . Most of these clinical trials 5 , 19 , 20 , 22 – 24 , 26 , but not all 21 , 27 , demonstrated that TRE results in weight loss. There are no studies that investigate the effect of engaging in a commercial weight loss program combined with TRE on body weight and cardiometabolic endpoints.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the non-time-restricted diet intervention, the time-restricted diet reduced weight, lean mass, and visceral fat ( p ≤ 0.05). Blood pressure, glycemic measure as HbA1c %, HOMA-IR, fasting glucose, and fasting insulin values were similar in both groups at the 12th week [ 32 ]. In a randomized controlled short-term fasting diet study conducted on male and female participants with central obesity, the intervention group diet monitored a daily 600 kcal energy intake twice a week, followed by five-day healthy eating advice.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that this type of practice in intermittent fasting types is promising in terms of cardiometabolic health due to its compatibility with the human circadian rhythm [ 35 ]. The dual-energy X-ray absorptiometry method has been used in many studies investigating the effectiveness of intermittent fasting diets in body weight management [ 31 , 32 ]. In this study, the bioelectric impedance method was used.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the study by Chow et al (5) builds on the small, but growing, body of literature that suggests that TRE can be implemented as an effective weight loss regimen in individuals with overweight and obesity. The randomized controlled data generated from this trial is important to the field, as it will help inform the design of longer term, larger scale studies of TRE in this population group.…”
mentioning
confidence: 99%